2005
DOI: 10.1590/s0034-89102005000200005
|View full text |Cite
|
Sign up to set email alerts
|

Antropometria de idosos residentes em instituições geriátricas, Fortaleza, CE

Abstract: Despite being institutionalized, there was seen a trend of decreasing anthropometric values in the study population similar to that found in other studies of elderly people but with different values. Thereby, such values could be useful in the nutritional assessment of institutionalized elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
65

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 14 publications
2
11
1
65
Order By: Relevance
“…25 This fact can be explained both by age and functional disability. 5 While in this study the high prevalence of physical inactivity was not significantly related to constipation ( p=1.000), and another study 21 reported the same findings, regular physical activity should be performed and is recommended by the World Gastroenterology Organization 26 as a way of managing intestinal constipation.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…25 This fact can be explained both by age and functional disability. 5 While in this study the high prevalence of physical inactivity was not significantly related to constipation ( p=1.000), and another study 21 reported the same findings, regular physical activity should be performed and is recommended by the World Gastroenterology Organization 26 as a way of managing intestinal constipation.…”
Section: Discussionmentioning
confidence: 45%
“…4 These changes cause functional changes in the body of the elderly individual, as they occur in almost all parts of the body and can lead to constipation. 5 This, in turn, is associated with factors such as advanced age, poor diet, inadequate fluid intake, physical inactivity, polypharmacy, and is related to a family history of constipation. 6,7 Constipation is not a disease or a sign but a symptom, and as such, may originate from various intestinal and extraintestinal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Assim como em outros estudos desenvolvidos no Brasil, 11,13,[15][16][17]24,25 neste estudo também se verificou maior frequência de idosos do sexo feminino. 18 Na literatura, a maioria dos estudos observou valores médios de peso e estatura superiores para o sexo masculino.…”
Section: Discussionunclassified
“…Entre esses países, destacam-se os Estados Unidos, a Inglaterra, a França, Itália e o México. [4][5][6][7][8][9][10] No Brasil, existem alguns estudos que investigaram as características antropométricas da população [11][12][13][14][15][16][17] Os idosos foram agrupados segundo sexo e grupo etário (60-69 anos, 70-79 anos e 80 e mais). As variáveis antropométricas foram apresentadas sob a forma de média, desvio-padrão e percentil (P5, P10, P25, P50, P75, P90 e P95).…”
Section: Introductionunclassified
“…A proporção de mulheres institucionalizadas foi significantemente maior que a de homens, como em outros estudos brasileiros 10,16 .…”
Section: I S C U S S ã Ounclassified